2020
DOI: 10.1088/1757-899x/796/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

TPM Maintenance Management Model Focused on Reliability that Enables the Increase of the Availability of Heavy Equipment in the Construction Sector

Abstract: The purpose of this paper is to present a maintenance study focused on total productive maintenance (TPM) and reliability-centered maintenance (RCM). Its approach is based on the first pillars of TPM, preventive and autonomous maintenance, as well as the FMEA analysis of RCM for maintenance analysis, which was conducted in this study. The implementation of TPM was successful in that various preventive maintenance (PM) policies assigned to the assets were implemented and it was demonstrated that TPM application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Ref. [33] afirmó que la gestión de mantenimiento preventivo pudó mejorar las condiciones de funcionamiento y detectar las posibles fallas potenciales que pueden ocasionar paradas en la producción.…”
Section: Discussionunclassified
“…Ref. [33] afirmó que la gestión de mantenimiento preventivo pudó mejorar las condiciones de funcionamiento y detectar las posibles fallas potenciales que pueden ocasionar paradas en la producción.…”
Section: Discussionunclassified
“…His research also showed that failures due to breakdown of parts make up 56 percent of total breakdowns, and the rest, 44 percent, are due to violations of regulatory parameters (Madzhov, 2019) . To lower maintenance costs, as well as improve the availability of equipment, some authors suggest implementation of total productive maintenance (TPM) and reliability-centered maintenance (RCM) concepts, which focus more on preventing breakdown than repairing equipment after it happened (Palomino-Valles et al, 2020;Bhushan et al, 2022;Spasojević-Brkić et al, 2022). In order to implement predictive maintenance, the most important part of TPM, the first step is the selection of critical breakdowns by analyzing failure data and the proper risk assessment of each kind of breakdown (Cicek et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Contractors reported an operative availability between 61% and 81% after a strategic plan was applied to improve it [14].…”
Section: Impact On the Skid Steer And Hydraulic Breaker Durabilitymentioning
confidence: 99%